2019
DOI: 10.1080/13696998.2019.1631832
|View full text |Cite
|
Sign up to set email alerts
|

Federal government-interest patent disclosures for recent top-selling drugs

Abstract: Objective: To provide updated evidence on government-interest patent disclosures in US patents for top-selling small-molecule drugs. Methods: IQVIA National Sales Perspectives data identified 300 top-selling drugs, defined by peak 2013-2017 US sales. For the 197 approved through New Drug Applications (NDAs), data were collected from a recently-released dataset of all patents listed in 1985-2016 Annual Editions of the FDA Orange Book. Data on patent assignees and Government Interest Statements (if any) were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…Of these, 295 (95%) had at least one patent in the Orange Book and 27 had a patent in the Orange Book that was associated with the research identified in this study (Table 8). This fraction is similar to the fraction of drugs with NIH-funded patents in the Orange Book identified using a variety of other methods (Li et al, 2017;Long, 2019;Sampat, 2006;Sampat & Lichtenberg, 2011;Stevens et al, 2011).…”
Section: Nih-funded Patents Associated With Approved Drugssupporting
confidence: 54%
“…Of these, 295 (95%) had at least one patent in the Orange Book and 27 had a patent in the Orange Book that was associated with the research identified in this study (Table 8). This fraction is similar to the fraction of drugs with NIH-funded patents in the Orange Book identified using a variety of other methods (Li et al, 2017;Long, 2019;Sampat, 2006;Sampat & Lichtenberg, 2011;Stevens et al, 2011).…”
Section: Nih-funded Patents Associated With Approved Drugssupporting
confidence: 54%
“…A 2019 study found that 75% of all U.S. Food and Drug Administration (FDA) approved drugs—excluding new vaccines, biologic medicines, and gene therapies—between January 2008 and December 2017 were fully funded and researched by private companies [ 6 ]. The results were comparable with those of an earlier study that found only 9% of new drugs approved between 1988 and 2005 had either a government interest statement disclosure or a government agency first-listed as a patent assignee [ 7 ]. Finally, research published in 2011 by Rohrbaugh et al found that the Bayh–Dole Act (Public Law 96–517) had been responsible for the transfer of federally funded research and intellectual property that had led directly to 153 FDA-approved drugs that were discovered, at least in part, by public-sector research from a total of 1541 approved therapies [ 8 ], less than 10% of the total.…”
Section: Introductionsupporting
confidence: 83%
“…For example, for the 12 approved products in our analysis that appear in the FDA Orange Book, the NIH-supported patents we identified accounted for only 5 of the 41 total patents listed as protecting these products. Furthermore, a 2019 analysis of 197 top-selling therapies found that only 10.2% had at least one patent recorded in the Orange Book with a government interest statement or U.S. government agency assignee [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Sampat and Lichtenberg examined “public sector” or “academic” patents related to drugs approved 1988–2005, finding that 9% of new drugs were associated with a public sector patent [ 7 ]. Similarly, Long reported that 8.6% of drugs had at least one patent with a “government-interest” statement [ 38 ] and Stevens et al estimated that from 1990–2007, 9.3% of new drugs were first patented in public sector research institutions [ 39 ].…”
Section: Discussionmentioning
confidence: 99%